Event-Based Fuzzy H∞ Control for Unreliable Nonlinear Networked Systems - Qu, Zifang; Du, Zhenbin; Zhang, Guangyong; Sun, Xiaohong (IEEE access, 2024)
The nonlinear Networked Control Systems (NCSs) analyzed in this study not only has packet loss, but also has induced-delay. For this kind of complex systems, this manuscript presents an effective scheme for addressing the Interval Type-2 (IT2) H_{∞ } fuzzy control based on event-triggered mechanism. By applying this scheme, the system can mitigate the effects of packet loss and induced-delay while achieving H_{∞ } performance. Specifically, this manuscript employs an IT2 fuzzy system for modeling the controlled plants, and introduces an event-triggered controller to ensure system stability. This approach aims to effectively manage the complexities introduced by packet loss and induced-delay in the control systems. Meanwhile, we adopt the Wirtinger inequality, slack matrices, and the free-weighting matrix to enhance the qualitative investigation of this proposed control system. In addition, the use of Lyapunov-Krasovskii Functional (LKF) enables derivation of steadiness analysis and facilitates achievement of H_{∞ } performance in the control system. Moreover, the proposed event-triggered control approach is validated through the use of two examples, demonstrating its efficacy in practical scenarios. Additionally, the manuscript highlights the advantages and strengths of the developed design, showcasing its effectiveness in addressing the challenges posed by packet loss and induced-delay in NCSs.